Early disappearance of tumor antigen-reactive T cells from peripheral blood correlates with superior clinical outcomes in melanoma under anti-PD-1 therapy. Issue 12 (21st December 2021) - Bochem, Jonas; Zelba, Henning; Spreuer, Janine; Amaral, Teresa; Gaissler, Andrea; Pop, Oltin T; Thiel, Karolin; Yurttas, Can; Soffel, Daniel; Forchhammer, Stephan; Sinnberg, Tobias; Niessner, Heike; et al.
Abstract : Background: Anti-programmed cell death protein 1 (PD-1) antibodies are now routinely administered for metastatic melanoma and for increasing numbers of other cancers, but still only a fraction of patients respond. Better understanding of the modes of action and predictive biomarkers for clinical outcome is urgently required. Cancer rejection is mostly T cell-mediated. We previously showed that the presence of NY-ESO-1-reactive and/or Melan-A-reactive T cells in the blood correlated with prolonged overall survival (OS) of patients with melanoma with a heterogeneous treatment background. Here, we investigated whether such reactive T cells can also be informative for clinical outcomes in metastatic melanoma under PD-1 immune-checkpoint blockade (ICB). Methods: Peripheral blood T cell stimulation by NY-ESO-1 and Melan-A overlapping peptide libraries was assessed before and during ICB in two independent cohorts of a total of 111 patients with stage IV melanoma. In certain cases, tumor-infiltrating lymphocytes could also be assessed for such responses. These were characterized using intracellular cytokine staining for interferon gamma (IFN-γ), tumor negrosis factor (TNF) and CD107a. Digital pathology analysis was performed to quantify NY-ESO-1 and Melan-A expression by tumors. Endpoints were OS and progression-free survival (PFS). Results: The initial presence in the circulation of NY-ESO-1- or Melan-A-reactive T cells which became no longer detectable during ICB correlated with validated, prolonged PFS (HR:0.1; p>0.0001) and OS (HR:0.2; p=0.021). An evaluation of melanoma tissue from selected cases suggested a correlation between tumor-resident NY-ESO-1- and Melan-A-reactive T cells and disease control, supporting the notion of a therapy-associated sequestration of cells from the periphery to the tumor predominantly in those patients benefitting from ICB. Conclusions: Our findings suggest a PD-1 blockade-dependent infiltration of melanoma-reactive T cells from the periphery into the tumor and imply that this seminally contributes to effective treatment.